2010
DOI: 10.1111/j.1526-100x.2010.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Growing Zostera marina (eelgrass) from Seeds in Land-Based Culture Systems for Use in Restoration Projects

Abstract: The use of aquaculture systems to grow the seagrass Zostera marina (eelgrass) from seeds for restoration projects was evaluated through laboratory and mesocosm studies. Along the mid-Atlantic coast of North America Z. marina seeds are shed from late spring through early summer, but seeds typically do not begin to germinate until the late fall. Fall is the optimal season to plant both seeds and shoots in this region. We conducted studies to determine if Z. marina seeds can be induced to germinate in the summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 52 publications
2
63
1
2
Order By: Relevance
“…These physical processes are potentially also important for seed dispersal and seedling retention in other submerged macrophytes (Koch et al 2010). Some previous data exist suggesting a direct seed burial effect on germination (Granger et al 2000, Tanner & Parham 2010, and our results from seedburied plots in December showing a high proportion of germinated seeds are consistent with a seed burial effect on germination (Fig. 1), although variability in the number of seeds recovered and the proportion germinated was high, especially for Spider Crab Bay.…”
Section: Role Of Seed Burialsupporting
confidence: 88%
“…These physical processes are potentially also important for seed dispersal and seedling retention in other submerged macrophytes (Koch et al 2010). Some previous data exist suggesting a direct seed burial effect on germination (Granger et al 2000, Tanner & Parham 2010, and our results from seedburied plots in December showing a high proportion of germinated seeds are consistent with a seed burial effect on germination (Fig. 1), although variability in the number of seeds recovered and the proportion germinated was high, especially for Spider Crab Bay.…”
Section: Role Of Seed Burialsupporting
confidence: 88%
“…Both Z. marina and Z. noltii seeds were found to germinate better at lower salinities with the maximum germination rate reached at salinity 1 (Hootsmans et al, 1987;Tanner and Parham, 2010). Yamaki et al (2006) found that the Z. marina seeds from both Tohoku and Kanto (Japan) reached the maximum germination rate in 10 d at salinity 0 and 20℃.…”
Section: Discussionmentioning
confidence: 96%
“…It is also a key component of eelgrass bed reconstruction methodology. Temperature and salinity play important roles in eelgrass seed germination (Orth and Moore, 1983;Conacher et al, 1994;Abe et al, 2008;Tanner and Parham, 2010). In this study, the germination rates of eelgrass seeds at different combinations of temperature and salinity were compared in order to lay the groundwork for establishing an eelgrass artificial seedling culture method.…”
Section: Introductionmentioning
confidence: 99%
“…Storing seedlings in aquaculture facilities, especially for seagrasses with viviparous seeds, may extend their period of availability (Tanner and Parham 2010;Statton et al 2012); however, techniques for medium-term maintenance of A. antarctica seedlings have yet to be developed. More importantly, there are no suitable aquaculture facilities to maintain seedlings in culture in Shark Bay.…”
Section: Discussionmentioning
confidence: 99%